Push selling : multicast messages to wireless device based on publish/subscribe model - Lim, Guey Long. (2008)
In this project, the student will survey the existing push technology that has been written in literatures, reexamining current push technology in commercial activity, identify the problems facing and investigate the possibility of proposing new solution to solve the limitation of current push technology.